2008
DOI: 10.1002/jmr.887
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein recognition as a first step towards the inhibition of XIAP and Survivin anti‐apoptotic proteins

Abstract: Apoptosis, also called programmed cell death, is a conserved mechanism inherent to all cells that sentences them to death when they receive the appropriate external stimuli. Inhibitor of apoptosis proteins (IAPs) are a family of regulatory proteins that suppress such cell death. XIAP is the most commonly studied member of the IAP family. It binds to and inhibits Caspases, an important family of apoptotic proteases. In addition, XIAP over-expression has been detected in numerous types of cancer. Smac/DIABLO, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Derivatives of embelin have been designed with higher affinity for XIAP BIR3 (for example, compound 6 g, K i ¼ 180 nM) to provide leads for further optimization . Nuclear magnetic resonance and molecular docking analyses confirmed that embelin interacts with several residues in the XIAP BIR3 domain with which Smac and caspase-9 bind (Nikolovska-Coleska et al, 2004;Obiol-Pardo et al, 2008). It remains to be determined whether embelin and its derivatives possess properties similar to SMCs in their ability to produce TNFa, or sensitize cancer cells to exogenous TNFa, and result in the proteosomal loss of cIAP1 and cIAP2.…”
Section: Additional Xiap Small Molecule Antagonistsmentioning
confidence: 99%
“…Derivatives of embelin have been designed with higher affinity for XIAP BIR3 (for example, compound 6 g, K i ¼ 180 nM) to provide leads for further optimization . Nuclear magnetic resonance and molecular docking analyses confirmed that embelin interacts with several residues in the XIAP BIR3 domain with which Smac and caspase-9 bind (Nikolovska-Coleska et al, 2004;Obiol-Pardo et al, 2008). It remains to be determined whether embelin and its derivatives possess properties similar to SMCs in their ability to produce TNFa, or sensitize cancer cells to exogenous TNFa, and result in the proteosomal loss of cIAP1 and cIAP2.…”
Section: Additional Xiap Small Molecule Antagonistsmentioning
confidence: 99%
“…Obiol-Pardo et al also used MD simulations for analyzing the protein-protein interactions appearing in the Smac/Diablo -XIAP complex but they only studied the BIR3 domain [57]. They used the cationic dummy approach [58] for maintaining the tetrahedral coordination of the zinc ion during the simulation while in our simulation, the tetrahedral coordination was preserved through bonded interactions with equilibrium values for angles, dihedrals, and bond lengths taken from a optimized geometry.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were acquired and refined trough a docking-scoring protocol. Docking was performed with our home-made program Dock_Dyn [19] by imposing the pharmacophore constraint to all conformations. This process selects only those conformations that fulfill the pharmacophore restriction speeding up the docking process.…”
Section: Methodsmentioning
confidence: 99%